Complex development of a digital platform of the agricultural economy - Amirova Elmira (EDP Sciences, 2021)
This paper describes the key points in the development of a digital platform for the agrarian economy of Russia. The main problems of transition of the Russian economy to a digital format of work, development, expansion of digital literacy, ways of solving the problems of digitalization of agricultural production are revealed. The creation of complex digital models of production processes in agriculture will increase the productivity of the business of agricultural producers. This requires generally valid agricultural production management systems with hundreds of parameters and analysis of big data, which includes the formation and algorithmization of management: equipment, devices, things, processes, money supply. Each platform is built on the management of the processes of crop production, livestock production, logistics of supply and sale. The basis of the digital platform which is being created as a knowledge platform that reflects the availability of professional staff in creating the necessary programs and providing farms with new IT opportunities to increase productivity. Thus, according to our research, improvement of digital infrastructure can be attributed to the main directions of development of digital technologies in the agricultural sector; updating the human resources of citizens by reducing the digital divide; orientation towards the use of domestic scientific and technical developments; development of domestic technologies correlated with scientific developments. A comprehensive scientific and technical program should also include a training system for the development and functioning of digital agriculture, and this requires the modernization of the entire educational process in agricultural educational institutions.